Detection of Cephalosporin and Fluoroquinolone Resistance Genes via Novel Multiplex qPCR in Fecal Salmonella Isolates From Northern Californian Dairy Cattle, 2002–2016 - Basbas, Carl; Byrne, Barbara A.; Chigerwe, Munashe; Escobar, Edlin D.; Hodzic, Emir; Pires, Alda F. A.; Pereira, Richard V. (Frontiers in Microbiology, 2021)
The objectives of this study were to evaluate the prevalence of extended spectrum β-lactamase (ESBL) genes, AmpC-type β-lactamase (ACBL) genes, and plasmid mediated quinolone resistance (PMQR) genes in Salmonella isolated at a Veterinary Medical Teaching Hospital microbiology laboratory, examine trends in presence of these resistance genes, and to explore the correlation between phenotypic resistance and presence of specific genes. The presence of ESBL, ACBL, and PMQR genes were detected using a single, novel multiplex qPCR. Only the genes blaCMY-2 and blaTEM were detected in the 110 Salmonella isolates tested. PMQR genes were not detected in isolates screened. Of 94 third-generation cephalosporin resistant isolates, representing eight serotypes, 48% (n = 45) were positive for blaCMY-2 only and 50% (n = 47) were simultaneously positive for blaCMY-2 and blaTEM. Two third-generation cephalosporin resistant isolates were tested negative for all β-lactamase genes in our qPCR assay and likely house ESBL genes not screened for by our qPCR assay. A logistic regression model revealed that for serotype Dublin isolates (n = 38) the odds ratio for testing positive for blaTEM when compared to all other serotypes was 51.6 (95% CI:4.01-664.03, p = 0.0029). For serotype Typhimurium (n = 9) the odds ratio for testing positive for blaTEM when compared to all other serotypes was 43.3 (95% CI:1.76-1000, p = 0.0216).Overall, our results suggest that the prevalence of resistance to cephalosporins and fluoroquinolones due to ESBLs, ACBLs, and PMQR genes present in bovine nontyphoidal Salmonella enterica isolates has remained relatively constant in the isolates screened over a 14-year period.